Exploring the effect of covid-19 on small and medium enterprises: early evidence from Sri Lanka - Robinson, J.; Kengatharan, N. (My University, 2020)
The exponential growth of the COVID-19 pandemic is of great global economic problems and has received magnificent worldwide attention. The vulnerability of the pandemic with lower economic immunity is greater in developing countries. The present study aims to explore the effects of the COVID-19 pandemic on SMEs in Sri Lanka. Data were marshalled with the aid of qualitative interviews from conveniently chosen 14 small and medium enterprises (SMEs). The study reveals that the mitigating strategies and protocols to combat the COVID-19 have come at high economic and human costs and gravely sullied the SMEs in Sri Lanka including the shortage of materials, decline in both global and local demand for their products and services, difficulties in repaying loan and interest, cancellation of orders, dire cash deficit (inflows) and lack of savings (even problems with payroll and utility bills), limitations in recalling the employees back to work, high cost in preventing workplace COVID-19 strategies, absence of new orders, etc. The COVID-19 pandemic is emotionally challenging for both employees and operators of the SMEs. The government relief and the best policies and guidelines to support the SMEs are indeed crucial for riding through the crisis. The present study further ensures the overarching importance of formulating after-effects COVID-19 economic revival policies. Needless to say, the resilience of the SMEs is greatly dependent on the concerted efforts of the government, SMEs operators and other policymakers.
Keywords: COVID-19; Mitigating strategies; SMEs; Sri Lanka